Molecular cloning and activity analysis of a seed-specific FAD2-1B gene promoter from Glycine max - Zhao, Y; Sha, W; Wang, Q Y; Zhai, Y; Zhao, Y; Shao, S L (Cellular and Molecular Biology, 2015)
Microsomal omega-6 fatty acid desaturase (FAD2-1B) is an enzyme that regulates the polyunsaturated fatty acid content in soybeans (Glycine max). In this study, the FAD2-1B gene was determined to be highly expressed in soybean seeds using quantitative real-time PCR(qRT-PCR). To investigate the expression pattern and activity of the FAD2-1B promoter, a 1929 bp 5'-upstream genomic DNA fragment, named PF, was isolated according to the soybean genomic sequence. Sequence analysis revealed the presence of many motifs related to seed-specific promoters in the PF fragment, such as E-box, SEF4, Skn-1 motif, AACACA, AATAAA and so on. Tobacco transgenics carrying the gus reporter gene driven by the PF and/or 35S promoters were confirmed by PCR and RT-PCR. qRT-PCR and histochemical GUS assays showed that the PF promoter could regulate gus gene accumulation in seeds and the expression level was higher than in other organs. In the meantime, it exhibited similar activity to the 35S promoter in seeds, which could be associated with seed-related cis-elements found in the 1-248 bp, 451-932 bp, and 1627-1803 bp regions of the promoter.